GROWTH AND CALORIFIC APPROXIMATION IN THE SPECKLED TROUT (Salvelinus fontinalis) - Job, S V (Indian Journal of Fisheries, 2015)
From the point of view of energy metabolism, appropriate measures of the rate of oxygen uptake would indicate the energy turnover or the capacity of the organism to perform external work in relation to its size and under the prevalent environmental conditions. Estimates of oxygen uptake when considered in conjimction with growth rate and calorific equivalent of the metabolic rate, would permit estimates of the total energy requirements of the individual. It has long been established, that the calorific equivalent of food consumed corresponds to the heat output plus the heat equivalent of excreta, and that such a measurement of metabolism can be verified also by indirect calorimetric methods based on the gas exchange of the animal.